2007
DOI: 10.1021/bm700843m
|View full text |Cite
|
Sign up to set email alerts
|

New Amphiphilic Lactic Acid Oligomer−Hyaluronan Conjugates: Synthesis and Physicochemical Characterization

Abstract: The "grafting onto" strategy was used to conjugate DL-lactic acid oligomers (OLA) to hyaluronan (HA) for the sake of developing novel degradable HA-based self-assembling polymeric systems. Grafting was achieved by reacting COCl-terminated OLA with cetyltrimethylammonium hyaluronate (CTA-HA) in dimethyl sulfoxide (DMSO). The resulting CTA-HAOLA conjugates were purified and turned to sodium form (Na-HAOLA) by dissolution in a phosphate buffer-DMSO mixture and successive dialyses against DMSO, ethanol, and water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Peaks at 1,149.01 cm −1 suggested the presence of C-O-C link bonds. FTIR characterization of WTPS showed the typical absorption patterns of polysaccharides (23)(24)(25). Absorption peaks at 1,149.01, 939.13, and 816.64 cm −1 and comparisons with previous results indicated that the polysaccharide consisted of pyranoside (26).…”
Section: Mw Determinationsupporting
confidence: 62%
“…Peaks at 1,149.01 cm −1 suggested the presence of C-O-C link bonds. FTIR characterization of WTPS showed the typical absorption patterns of polysaccharides (23)(24)(25). Absorption peaks at 1,149.01, 939.13, and 816.64 cm −1 and comparisons with previous results indicated that the polysaccharide consisted of pyranoside (26).…”
Section: Mw Determinationsupporting
confidence: 62%
“…For relatively small HA derivatives or fragments, HPLC [8][9][10][11][12] or HPLC-MS [13,14] have been employed. For large underivatized HA, size-exclusion chromatography (SEC) [15][16][17][18][19][20][21][22], SEC combined with viscometry [23][24][25], SEC combined with light scattering (LS) detection (SEC-LS) [23][24][25][26][27][28][29][30][31][32], SEC combined with MALDI-MS (SEC-MALDI-MS) [33][34][35] have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, HA can be converted into a DMSO-soluble salt which can undergo esterification with activated compounds such as acylchloride carboxylates [164].…”
Section: Modification Of Ha Hydroxyl Groupsmentioning
confidence: 99%